Exosomal hsa_circRNA_047733 integrated with clinical features for preoperative prediction of lymph node metastasis risk in oral squamous cell carcinoma. (9th November 2022) - Deng, Qingrong; Chen, Yujia; Lin, Lisong; Lin, Jing; Wang, Huiying; Qiu, Yu; Pan, Lizhen; Zheng, Xiaoyan; Wei, Lihong; Wang, Jing; Liu, Fengqiong; He, Baochang; et al.
Abstract: Background: To evaluate whether exosomal circRNAs could serve as diagnostic biomarkers for the accurate preoperative prediction of lymph node metastasis (LNM) risk in oral squamous cell carcinoma (OSCC) patients. Methods: A combinative strategy of exosomal circRNAs microarray and qRT‐PCR verification was employed to dig LNM‐related circRNA signatures. Then, a dynamic nomogram was developed based on candidate circRNAs and preoperative clinical features and the calibration, discrimination, and clinical use of the nomogram were evaluated. Results: According to the microarray, three circRNAs derived from the tumor were associated with preoperative LNM risk, including hsa_circRNA_047733, hsa_circRNA_024144 and hsa_circRNA_403472. The hsa_circRNA_047733 was further verified to be significantly downregulated in patients with LNM (+) as compared with those with LNM (−) ( p = 0.007). Patients with the higher expression of hsa_circRNA_047733 showed a lower risk of LNM (multivariate‐adjusted OR = 0.22, 95%CI: 0.06–0.83). The bioinformatics prediction showed that hsa_circRNA_047733 might sponge miR‐4464/miR‐4748 to regulate RPS21 expression. A dynamic nomogram integrating exosomal hsa_circRNA_047733 with five clinicopathological characteristics (tumor site, leukocyte level, maximum tumor diameter, and LNM reported by MRI and preoperative biopsy differentiation) was developed. The model displayed an excellent discrimination ability (AUC = 0.868, 95%CI: 0.781–0.955) and great calibration. The decision curve revealed a higher net benefit superior to the baseline model at an 80% threshold probability. Conclusion: The data provide preliminary evidence that exosomal hsa_circRNA_047733 might be a novel biomarker for the LNM of OSCC. The hsa_circRNA_047733‐based dynamic nomogram could serve as a convenient preoperative assessment tool to predict the risk of LNM for OSCC patients.